2022
DOI: 10.1101/2022.06.28.497938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leaf specific overexpression of a mitochondrially-targeted glutamine synthetase in tomato increased assimilate export resulting in earlier fruiting and elevated yield

Abstract: To identify potential strategies for increasing the efficiency of tomato leaf metabolism, with a focus on the links between nitrogen/carbon metabolism, we explored a diel Flux Balance Analysis (FBA) model of a source leaf in which the metabolic output was varied up to the theoretically-achievable maximum. We noticed a potentially interesting switch in the use of glutamine synthetase (GS) isoforms -from the chloroplast isoform to the mitochondrial one- for nitrogen assimilation. To further explore this predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…In tomato, several genes involved in N-response have been identified through functional genomic studies. Reverse genetic approaches have been used to characterise several genes involved in N uptake (Fu et al, 2015), assimilation (Vallarino et al 2022) or remobilization (Cao et al, 2022). In addition, many transcriptomic (Renau-Morata et al 2021, Sunseri et al 2023), proteomic (Xun et al, 2020) and metabolomic (Urbanczyk-Wochniak and Fernie, 2005; Larbat et al, 2014; Sung et al, 2015) approaches have identified differentially expressed genes and metabolic pathways involved in nitrogen metabolisms.…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, several genes involved in N-response have been identified through functional genomic studies. Reverse genetic approaches have been used to characterise several genes involved in N uptake (Fu et al, 2015), assimilation (Vallarino et al 2022) or remobilization (Cao et al, 2022). In addition, many transcriptomic (Renau-Morata et al 2021, Sunseri et al 2023), proteomic (Xun et al, 2020) and metabolomic (Urbanczyk-Wochniak and Fernie, 2005; Larbat et al, 2014; Sung et al, 2015) approaches have identified differentially expressed genes and metabolic pathways involved in nitrogen metabolisms.…”
Section: Introductionmentioning
confidence: 99%